Constructing a Sustainable Roller Compacted Concrete Using Waste Demolished Material as Replacement of Cement: A Review (Journal of Engineering, 2023)
Roller Compacted Concrete is a type of concrete that is environmentally friendly and more economical than traditional concrete. Roller Compacted Concrete is typically used for heavy-duty and specialist constructions, such as hydraulic structures and pavements, because of its coarse surface. The main difference between RCC and conventional concrete mixtures is that RCC has a more significant proportion of fine aggregates that allow compaction and tight packing. In recent years, it has been estimated that several million tons of waste demolished material (WDM) produced each year are directed to landfills worldwide without being recycled for disposal. This review aimed to study the literature about creating a Roller-Compacted Concrete (RCC) mix with modified engineering properties with favorable environmental impact, so it was focused on investigating using different proportions of waste (Glass, Brick, and Marble), which are the most waste-demolished materials (WDM) widely in the world, as a partial substitute of cement. Then, study the influence on the durability and mechanical strength of (RCC) produced with and without these waste powders.